Environmental Impacts of Automotive Air Conditioning System Maintenance Practices Embraced by Service Technicians in Niger State, Nigeria - Ogunleye, U O; Audu, R; Hassan, A M; Abdulkadir, M (Journal of Sustainability and Environmental Management, 2022)
This research work examined the environmental impacts of automotive air conditioning system maintenance practices embraced by service technician in Niger State, Nigeria.  The study sought out the problem associated with automotive air conditioning maintenance practices and the way of improving automotive air conditioning system maintenance practices by automotive air conditioning services technicians in Niger State. Two research questions and two hypotheses guided the study. A descriptive survey research designed was adopted for the study. A total population of 155 respondents comprises of 97 highly experienced registered air conditioning service technicians and 58 moderately experienced registered air conditioning service technicians in Niger State. The respondents were selected according to the year of service, which was 1-14 years for moderately experienced and 15 above for highly experienced service technicians. Due to manageable sizes of the respondents, the entire population was used i.e no sampling techniques was utilized for the study. A structured questionnaire title “Automotive Air Conditioning System Maintenance Practices Questionnaire” was faced validated by three experts (one lecturer from Department of Industrial and Technology Education, Federal University of Technology Minna, one expert from Ministry of Environment Niger State and one expert from Ministry of Health Niger State). The questionnaire was pilot tested using 30 automotive air conditioning service technicians from Abuja. The data collected were analyzed using Cronbach Alpha Statistics and its yielded to 0.71 reliability coefficient. Mean and standard deviation were used to analyze the research questions and hypotheses were tested at 0.05 level of significance using z-test statistics. The numerical values obtained from the responses of the respondents were tabulated and analyzed using statistical package for social science (SPSS) version 23. The findings among other revealed that  inhalation of concentration refrigerant vapour is dangerous and can be fatal, exposure to level of fluorocarbons above recommended exposure levels can results in loss of concentration and drowsiness, inhaling refrigerants adds to the effect of chronic illness. It is recommended amongst other that hazardous automotive air conditioning waste generated by automotive service technicians’ shops should always be removed by licensed personnel under the supervision of environmental agencies. Manufacturer instructions on refrigerants should be followed by technicians.